How Is The Level Of Knowledge Of Medical Recorders And Health Information About Snomed Ct Towards Medical Records Transformation? Case Study In Tasikmalaya Hospital - Ara Noerahmy; Ida Wahyuni (Media Informasi, 2026)
Background: One of the health problems in Indonesia is fragmented health data. Today, interoperability in Indonesia is still a barrier.SNOMED-CT is a new policy to be implemented in hospitals in Indonesia. This knowledge of SNOMED-CT has a great impact on the performance of administrator health information management, it affects the information generated in medical records especially in support of medical services. Objectives: The aim of this study is to learn the knowledge of administrator health information management on SNOMED-CT at the Tasikmalaya City Hospital. Methods: A type of quantitative research with a descriptive approach. The population in this study is medical recorders and health information. Sampling technique using simple random sampling. Data collection method using a questionnaire. Data analysis using univariate analysis. Conducting a frequency distribution analysis of the level of knowledge of medical recorders and health information in the city hospital of Tasikmalaya in 2024. Results: The level of knowledge of medical recorders and health information about SNOMED-CT belongs to a sufficient category of 45%, a category of less than 28% and a good category of 27%. Conclusion: Medical recorder knowledge and health information on SNOMED-CT in Tasikmalaya City Hospital in category sufficient. To support administrator health information management insight into SNOMED-CT, independent learning can be done using a healthy website, webinars, training and workshops